2023
DOI: 10.1038/s41598-023-39177-4
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural network approach for prediction of AuNPs biosynthesis by Streptomyces flavolimosus, characterization, antitumor potency in-vitro and in-vivo against Ehrlich ascites carcinoma 

Noura El-Ahmady El-Naggar,
Nashwa H. Rabei,
Mohamed F. Elmansy
et al.

Abstract: Gold nanoparticles (AuNPs) have emerged as promising and versatile nanoparticles for cancer therapy and are widely used in drug and gene delivery, biomedical imaging, diagnosis, and biosensors. The current study describes a biological-based strategy for AuNPs biosynthesis using the cell-free supernatant of Streptomyces flavolimosus. The biosynthesized AuNPs have an absorption peak at 530–535 nm. The TEM images indicate that AuNPs were spherical and ranged in size from 4 to 20 nm. The surface capping molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 107 publications
1
4
0
Order By: Relevance
“…8B ). 30,62 The TEM/SAED results were consistent with the XRD results. The average particle size of MSK03-AuNPs was measured to be 23.2 ± 10.7 nm, with a size range varying from 7.1 to 40.0 nm ( Fig.…”
Section: Resultssupporting
confidence: 82%
“…8B ). 30,62 The TEM/SAED results were consistent with the XRD results. The average particle size of MSK03-AuNPs was measured to be 23.2 ± 10.7 nm, with a size range varying from 7.1 to 40.0 nm ( Fig.…”
Section: Resultssupporting
confidence: 82%
“…Therefore, it can be concluded that ANN exhibits superior predictive abilities capacity for the optimal levels of GNPs biosynthesis. The observed output can be attributed to the efficacy of ANN to provide good performance can be attributed to the repeated training of the neurons for different physicochemical factors 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 displays the actual and coded levels of the four variables, the experimental and predicted values for GNPs, accompanied by their corresponding residuals. According to the CCD results of El-Naggar et al 25 , the GNPs produced using the cell-free supernatant of Streptomyces flavolimosus showed notable changes in GNPs color as a result of the optimal levels of various independent variables during the optimization process. Based on the variance of the four variable levels, the results revealed that the biosynthesized GNPs exhibited a range of values, beginning from 190.93 to 778.74 µg/mL.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations